Development of Anthelmintic Resistance Detection Methods of Gastrointestinal Nematodes on Livestock - Dyah Haryuningtyas (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2008)
The intensive usage of anthelmintic in most of farms led to resistances of livestock gastrointestinal nematodes against anthelmintic.  Many  reports  of  resistance  that  increased  every  year  happen  following  the  continuing  helminth  control programmes. The succesful implementation of helminth control programmes that designed to minimize the development of resistance in nematode populations depends on the availability of effective and sensitive method for its detection and monitoring. A variety of in vivo and in vitro tests have been developed for detecting nematode population resistance to the main  anthelmintic groups. This paper will discuss the development of detection method of anthelmintic resistance based on conventional and molecular approach according to their strengths and weakness.   Key words: Anthelmintic resistance, detection method, conventional, molecular, nematode